DEVELOPING THE CONCEPT OF STATE CIVIL APPARATUS PROFESSIONALISM IN THE RECRUITMENT PROCESS FROM A SHARIA PERSPECTIVE - Fathurrahman, Rezki Amalia; Abdullah, Muhammad Wahyuddin; Parmitasari, Rika Dwi Ayu; Fathurrahman, Fathurrahman (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2025)
The research aims to discover how to build the concept of professionalism of State Civil Apparatus from a Sharia perspective when conducting the recruitment process. The research method used is a qualitative approach to interview techniques for how to build the concept of State Civil Apparatus professionalism during the recruitment process according to Sharia based on the experiences of people who have applied for work, for example, the experience of participating in applying for work and following the recruitment process of Civil Servant Candidates whose informants are three people from postgraduate students of UIN Alauddin Makassar. The results of the study found that the professionalism of State Civil Apparatus is associated with a Sharia perspective, so the two important things that a professional State Civil Apparatus must possess are competence and integrity, then connected with three principles that are fulfilled, namely justice, honesty, and trustworthiness in order to fulfill accountability and according to criteria and benefits for organizations and society in providing the best service because it uses a Computer Assisted System (CAT) system so that participants and the general public can see the value directly so that the intention to commit fraudulent practices will not be carried out because the general public sees the value of participants can increase public trust.